The Triple Helix in Higher Education as A Zone for Character Education - Wijaya, Krisna; Izzati, Nida Rafiqa; Maharani, Syifa (el-Tarbawi, 2023)
In the modern era, the erosion of values and character among students due to technological advancements requires an ideal educational concept that maximizes character education. This study explores an educational concept that synergizes mosques, Islamic boarding schools, and universities in one unit-triple helix. Employing a library approach, the data sources in this study are printed and digital texts, as well as books and manuscripts. The findings of this study reveal that the concept of education which combines the natures of mosques, Islamic boarding schools, and universities (triple helix) as foundational pillars plays a pivotal role in shaping an individual's character through exemplary practices. Within the concept of the mosque, the education is to maximize various activities related to the mosque. In the Pesantren (Islamic boarding school) concept, education focuses on the application of the Pesantren system within the university education curriculum. Meanwhile, the concept of university refers to the Islamization of science, as seen in the curriculum of Universitas Darussalam Gontor, Indonesia.